Manipulating exciton transport in a two-dimensional transition metal dichalcogenide semiconductor - Wong, Yi Ren (Nanyang Technological University, 2023)
Harnessing exciton transport in solid-state devices is a scientific and technological challenge. If achieved, it could enable energy efficient devices and transform modern optoelectronics. This is however currently limited by the short exciton lifetime and low exciton mobility in many materials. The discovery of 2D materials however, provided a platform for achieving exotic states of condensed matter due to its unique quantum properties, otherwise absent in conventional semiconductors. Transition Metal Dichalcogenide (TMD) semiconductors in particular, are highly versatile and host excitons with large exciton binding energy which allows them to be observed even at high temperatures, making them a promising system to manipulate exciton transport. Utilizing a combination of real-space imaging, spatially-resolved and time-resolved spectroscopic techniques, the photoluminescence (PL) and reflectance signatures are studied in large area monolayer MoS2 transistor devices. By using an electrostatic backgate, we reveal ultrafast and long-range propagation of excitons at low electron or hole doping concentrations. The excitons exhibit a hydrodynamic-like transport, driven by strong exciton-exciton interactions, in contrast to typical diffusive transport under normal conditions. The insights gained from this study could provide a starting foundation to further understand excitonic interactions in TMDs, and control the behaviour of excitons with an external electric or magnetic field in novel 2D TMD semiconductors. This may be important for paving the way to realize exciton-based circuitry and ultrafast optoelectronic devices.